Siklus Konversi Teaching Factory Manufacturing of Electronic (TFME) Politeknik Negeri Batam - Mega Mayasari; Irsutami Irsutami; Muhammad Irsyad Halim (Pusat P2M Politeknik Negeri Batam, 2022)
This study aims to find an accurate picture of all production activities that run at the Batam State Polytechnic Teaching Factory Laboratory through system and procedure documentation whose results become the basis for designing systems and procedures and producing procedures in the production cycle that have considered internal control aspects at the Batam State Polytechnic Teaching Factory Laboratory. The research method used is descriptive qualitative. This research began with brainstorming with the Teaching Factory manager on the ongoing systems and procedures to get an overview of the existing conditions with survey procedures through interviews with the TFME manager. The next stage is to survey the parts related to production, starting from order acceptance, production, and post-production. The object of research is the production cycle that occurs in TFME involving several procedures, namely production order procedures, purchase requisition procedures, price quote request procedures and supplier selection, purchase order procedures, purchase return procedures, procedures for requesting and releasing goods from the warehouse, production monitoring procedures and cost accounting, procedures for returning goods at the warehouse, procedures for recording working hours and direct labor costs and procedures for finished products and recording of factory overhead charges. The survey results were then documented in procedures and continued with analysis to be carried out to the procedure design stage. The results of the documentation and analysis show that almost all procedures do not pay attention to internal control aspects, which consist of segregation of functions, authorization systems, and sound practices.